2020
DOI: 10.1007/s00167-020-06341-6
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted total knee arthroplasty is associated with a learning curve for surgical time but not for component alignment, limb alignment and gap balancing

Abstract: Purpose The application of robotics in the operating theatre for total knee arthroplasty (TKA) remains controversial. As with all new technology, the introduction of new systems is associated with a learning curve and potentially associated with extra complications. Therefore, the aim of this study is to identify and predict the learning curve of robot-assisted (RA) TKA. Methods A RA TKA system (MAKO) was introduced in April 2018 in our service. A retrospective analysis was performed of all patients receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
63
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 23 publications
10
63
2
2
Order By: Relevance
“…The first robotic system in orthopedic surgery is Robodoc, which has been used for TKA and total hip arthroplasty since 1992 20 . However, the application of this robotic system was limited because of increased operative time, insufficient versatility and technical complexity 21–23 . The objective of the robotic‐assisted TKA system is to provide a tool for surgeons to accurately resect bone and accurately select and balance implant and soft tissue placement 24–26 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first robotic system in orthopedic surgery is Robodoc, which has been used for TKA and total hip arthroplasty since 1992 20 . However, the application of this robotic system was limited because of increased operative time, insufficient versatility and technical complexity 21–23 . The objective of the robotic‐assisted TKA system is to provide a tool for surgeons to accurately resect bone and accurately select and balance implant and soft tissue placement 24–26 .…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the robotic‐assisted TKA system is to provide a tool for surgeons to accurately resect bone and accurately select and balance implant and soft tissue placement 24–26 . To date, multiple robotic‐assisted TKA systems, such as Mako (Stryker), Navio PFS (Plymouth) and Robodoc (CurexoTechnology), have been clinically used 22,27,28 . Until now, however, there have not been any robot‐assisted TKA systems approved by the National Medical Products Administration of China.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6] Robotically assisted TKA was thus developed to promote mechanical alignment, accuracy of bone resection, soft tissue protection, and implant survivorship and implant stability. [7][8][9][10] In this connection, our previous studies showed that a novel HURWA robotic-assisted TKA system (BEIJING HURWA-ROBOT Technology Co. Ltd) could enhance the accuracy of bone resection in terms of resection angles and levels in the sawbone and the sheep models. 11,12 The procedures of robotic-assisted TKA system consists of the following steps: preoperative computed tomography (CT) scanning of lower limbs, three-dimensional (3D) reconstruction of CT data of lower limbs, CT-based planning, surgical planning depending on the 3D CT model, and the act of performing robotic-assisted TKA.…”
mentioning
confidence: 99%